Improved two-phase flow boiling in a minichannel heat sink for thermal management of information and communication technology (ICT) equipment. (25th November 2020) - Hong, Sihui; Dang, Chaobin; Hihara, Eiji; Sakamoto, Hitoshi; Wada, Mizuki
Highlights: A radial expanding minichannel heat sink employing flow boiling for ICT equipment was proposed. Effects of cut-off and gap structures on mitigating reversal flow were verified with visualization. Local boiling performance and heat transfer enhancement of REMHS were both evaluated. Dynamic temperature fluctuations and temperature uniformity in REMHS was revealed. Static and dynamic pressure drop characteristics by adding cut-off and gap structures were analyzed. Abstract: Thermal management systems play a significant role in dissipating heat and guaranteeing the safety of facilities. For information and communication technology (ICT) systems, a highly reliable operation depends on accurate thermal control, including the maximum temperature attained and the uniformity of temperature of the semiconductor devices. In the literature, two-phase flow boiling devices have been proposed as an efficient solution for addressing this concern; however, the application of such devices is still fraught with serious challenges owing to the unstable flow boiling. This study aims at solving the problem of undesired heat transfer deterioration triggered by two-phase flow instability in ICT systems. Based on our previous proposed radial expanding minichannel heat sink (REMHS), we tested the effects of a cut-off structure and a gap structure on further stabilizing the flow boiling and enhancing heat transfer performance. The cut-off structure is employed in the flow direction to relieve the rapid expansion of vapor slugs in the minichannels. This elevated the heat transfer coefficient of the REMHS by nearly two-fold under high heat flux conditions and effectively eliminated the local hotspot on the heat sink. The overheating at the downstream of the REMHS, in terms of temperature, decreased by 55% from 29 to 13 K at a heat flux of 220 kW/m 2 . Moreover, a better wall temperature uniformity was obtained. The gap structure was found effective in liquid–vapor separation that maintains the temperature fluctuations below 0.6 K. By suppressing the detrimental reversal flow with the two proposed techniques, the REMHS achieved a high flow boiling heat transfer capability over a wide range of operating conditions and met the requirement of the ICT equipment thermal management system.